2014
DOI: 10.1007/s13202-014-0136-8
|View full text |Cite
|
Sign up to set email alerts
|

A more superior preformed particle gel with potential application for conformance control in mature oilfields

Abstract: The present work presents a nanocomposite preformed particle gel for conformance control in mature oilfields. This product was observed to have a better performance than conventional hydrogels without nanomaterials. Preformed particle hydrogel was designed by the reaction of monomer, initiator, crosslinker, additives, and calcium montmorillonite nanomaterial, whereas conventional hydrogel is designed from just monomer, initiator, crosslinker and additives. The presence of nanomaterial in hydrogel design afford… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
44
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 20 publications
0
44
0
6
Order By: Relevance
“…However, most of the oil fields water shutoff polymer gels still exhibit undesirable viscoelastic characteristics. Due to low viscoelastic properties, oil field engineers determined that incorporating solid micro particles and nanomaterials in water shutoff polymer gels enhances their viscoelastic characteristics …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of the oil fields water shutoff polymer gels still exhibit undesirable viscoelastic characteristics. Due to low viscoelastic properties, oil field engineers determined that incorporating solid micro particles and nanomaterials in water shutoff polymer gels enhances their viscoelastic characteristics …”
Section: Introductionmentioning
confidence: 99%
“…Due to low viscoelastic properties, oil field engineers determined that incorporating solid micro particles and nanomaterials in water shutoff polymer gels enhances their viscoelastic characteristics. [10][11][12][13][14][15][16] The present study develops hybrid gravitational search algorithm (GSA) and support vector regression (SVR)-based models for estimating the elastic modulus G′ and viscous modulus G″ of MONTH 2019 THE CANADIAN JOURNAL OF CHEMICAL ENGINEERING 1 coal fly ash (CFA) polymer gel systems for water shutoff treatment during EOR operations. In our laboratory study, we introduced CFA as a reinforcing solid material in the polyacrylamide (PAM) gelling solutions cross-linked by polyethyleneimine (PEI).…”
Section: Introductionmentioning
confidence: 99%
“…Since PPGs were more successful than in situ gels in controlling unwanted water, the present paper mainly focused on physical and chemical properties of the synthesized PPG, which is basically attributed to the approach to be utilized in the synthesis process. The synthesis approach of PPG and saltwater properties in which PPG is placed can affect PPG performance (Tongwa and Baojun 2015). Hitherto, many attempts have been made to synthesize PPGs and to examine their behavior under different conditions by many researchers.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the network parameters and absorbency changed very sharply with changing pH value. Tongwa et al (Tongwa and Baojun 2015) synthesized a preformed particle gel with calcium montmorillonite as a nanomaterial and disclosed that the presence of the nanomaterial in hydrogel causes a remarkable improvement in gel properties and its behavior in comparison with hydrogels without any nanomaterial. Pacheco et al (2014) prepared hydrogels from acrylamide and sodium methacrylate (NMA) by solution polymerization and examined the swelling behavior of hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…introduced hydrophobic monomer α‐methyl styrene into reaction system to prepare the nonhybrid HPGs by inverse emulsion polymerization, and they noticed that salinity, temperature, labile crosslinker content, and DCPM content influence the viscosity of DCPM aqueous dispersions. Tongwa and Bai pioneered the incorporation of nanomaterial into degradable particles, and observed that swelling performance, viscosity of the post‐degraded gels, and long‐term thermal resistance of nanocomposite gels are improved by several orders of magnitude against the hydrogels without nanomaterial. However, to the best of our knowledge, the degradation mechanism of both hybrid and nonhybrid HPGs and the effect of their thickening power on oil recovery have not been unraveled yet.…”
Section: Introductionmentioning
confidence: 99%